2021
DOI: 10.1155/2021/6618394
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Coinfection of Urogenital Schistosomiasis and Soil-Transmitted Helminthiasis among Primary School Children in Biase, Southern Nigeria

Abstract: Schistosomiasis and soil-transmitted helminthiasis (STH) are neglected tropical diseases (NTDs) that cause chronic infections and ill health. The study was carried out to determine the current infection status and risk factors associated with Schistosoma haematobium and soil-transmitted helminth (STH) coinfection among school children in Biase Local Government Area (LGA), Cross River State, Nigeria. A cross-sectional study was carried out. Urine and fecal samples were randomly collected from 630 school childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The IGS-Sh-LAMP showed 100% specificity with no crossreactivity against S. mansoni or any of the other included soiltransmitted helminth targets. This finding is of medical importance as coinfections often occur in S. haematobium endemic areas resulting in co-existence of different parasites in field samples (Opara et al, 2021). These results align with the study of Gandasegui et al (2015) in which a panel of different parasites including helminths and protozoa was examined.…”
Section: Discussionsupporting
confidence: 83%
“…The IGS-Sh-LAMP showed 100% specificity with no crossreactivity against S. mansoni or any of the other included soiltransmitted helminth targets. This finding is of medical importance as coinfections often occur in S. haematobium endemic areas resulting in co-existence of different parasites in field samples (Opara et al, 2021). These results align with the study of Gandasegui et al (2015) in which a panel of different parasites including helminths and protozoa was examined.…”
Section: Discussionsupporting
confidence: 83%
“…An earlier study reported that 90.8% of those infected with soiltransmitted helminths live in unfavorable environmental conditions [11]. The study also showed that the personal hygiene of the respondents was poor and worm eggs were found in their feces [12]. As the environment is one of the main risk factors in soil-transmitted helminth infections, Mlaten Village, Mojokerto, East Java was an ideal research location because the environment largely consists of agricultural areas and the majority of the people work as traditional cattle breeders.…”
Section: Introductionmentioning
confidence: 87%
“…Other factors include lack of portable water, fishing, swimming, and washing in the rivers, and poverty. To tackle this issue, the implementation of mass drug therapy, molluscicides and an effective control strategy initiative as seen in Egypt, Japan and Tunisia should be considered [45]. This approach will prevent reinfection of the disease, reduce the frequency of infection after treatment, and reduce drug resistance by the parasite [45].…”
Section: 21mentioning
confidence: 99%